Energy detection of unknown deterministic signals in κ-μ and η-μ generalized fading channels with diversity receivers - Annamalai, A.; Olaluwe, A. (2014 International Conference on Computing, Networking and Communications (ICNC), 2014)
In this article, we present an alternative moment generating function (MGF) based method for evaluating the receiver operating characteristics (ROC) of diversity energy detectors in a generalized fading environment. In contrast to the existing approaches that are based on either the circular contour integral and/or infinite series representations of the generalized Marcum Q-function Q u (.,.), we utilize an exponential-type integral for Q u (.,.) to facilitate the statistical averaging task over the independent and non-identically distributed (i.n.d) fading signal-to-noise ratios (SNRs). This leads to a very compact, exact, and an efficient solution for computing the average detection probabilities of diversity enabled energy detectors in a myriad of fading environments especially for the practical cases of square law selection (SLS) and square-law combining (SLC) diversity receivers with i.n.d and correlated fading statistics. Our unified analytical framework also encapsulates the existing results for Rayleigh, Nakagami-m, Nakagami-q and Rice fading environments by appropriate substitutions of the fading parameters in the κ-μ and η-μ generalized stochastic channel models.